Microinvasive mitral valve repair with transapical mitral neochordae implantation - Bergonzoni, Emma; D’Onofrio, Augusto; Mastro, Florinda; Gerosa, Gino (Frontiers in Cardiovascular Medicine, 2023)
Microinvasive cardiac surgery includes procedures performed off-pump, on the beating heart, with limited or absent skin incision and that rely on live imaging techniques. Transapical off-pump beating heart neochords implantation allows to repair severe mitral valve regurgitation due to leaflet prolapse or flail with live three-dimensional echo guidance. This procedure has shown good results up to 5-year and can be considered as a valid alternative to conventional surgery in selected patients with high prediction of success based on clinical and anatomical considerations. Aim of this review is to describe devices, indications, patient's screening process, clinical and echocardiographic results and future perspectives of this procedure.